PENGARUH BIAYA USAHATANI BUAH NAGA TERHADAP KEUNTUNGAN PARA PETANI BUAH NAGA DI DESA TEMUREJO KECAMATAN BANGOREJO KABUPATEN BANYUWANGI - Anggun Norma Isnanda; Hety Mustika Ani; Bambang Suyadi (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This study aims to determine the Influence of Dragon Fruit Farming Costs on Profit of the Dragon Fruit Farmers in Temurejo Village, Bangorejo Sub-district, Banyuwangi District. The research approach used in this research is quantitative research. Research subjects are dragon fruit farmers in the Village Temurejo Bangorejo Banyuwangi as many as 50 farmers. Data collection methods used consisted of questionnaire method, observation, interview, and document. The results showed that there is a significant effect of dragon fruit cost variable on the profit of dragon fruit farmers in Temurejo Village, Bangorejo Sub-district, Banyuwangi Regency is 78.6%, while the remaining 21.4% is influenced by other independent variables which are not examined in this research Namely the use of technology, production quality, and production consumer.